2013
DOI: 10.1002/da.22132
|View full text |Cite
|
Sign up to set email alerts
|

DIFFICULT-TO-TREAT PEDIATRIC OBSESSIVE-COMPULSIVE DISORDER: FEASIBILITY AND PRELIMINARY RESULTS OF A RANDOMIZED PILOT TRIAL OFd-CYCLOSERINE-AUGMENTED BEHAVIOR THERAPY

Abstract: In this preliminary study, DCS-augmented ERP produced significant improvements in OCD severity from posttreatment to 1-month follow-up, relative to a placebo control condition, in severe and difficult-to-treat pediatric OCD. The significant effect on obsessional severity suggests that DCS augmentation might be associated with enhanced modification of obsessional thoughts during ERP, and warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 38 publications
(59 reference statements)
2
65
2
1
Order By: Relevance
“…The only published DCS studies have involved children and adolescents with obsessive-compulsive disorder (Storch et al 2010;Farrell et al 2013). Storch and colleagues randomized 30 8-17-year-old youth to either CBT and DCS or CBT and placebo for seven exposure sessions.…”
Section: Dcs As An Adjunct To Psychotherapy For Ptsdmentioning
confidence: 99%
“…The only published DCS studies have involved children and adolescents with obsessive-compulsive disorder (Storch et al 2010;Farrell et al 2013). Storch and colleagues randomized 30 8-17-year-old youth to either CBT and DCS or CBT and placebo for seven exposure sessions.…”
Section: Dcs As An Adjunct To Psychotherapy For Ptsdmentioning
confidence: 99%
“…Behavioural treatments for OCD have been repeatedly demonstrated to be effective (Rosa-Alcázar, Sánchez-Meca, Gómez-Conesa, & Marín=Martínez, 2008), even in the most severe and refractory cases Boschen, Drummond, & Pillay, 2008;Farrell et al, 2013). Despite this success, increasing research interest (Boschen, 2008), and applications of technological advances to the treatment of OCD (Lind, Boschen, & Morrissey, 2013), there are many for whom treatment is ineffective (Fisher & Wells, 2005), and predictors of treatment response have been difficult to identify (Boschen, Drummond, Pillay, & Morton, 2010;Boschen & Farrell, 2011).…”
mentioning
confidence: 99%
“…Results of this study showed DCS-augmented exposure, and response prevention produced significant improvements in OCD severity relative to a placebo control in severe and difficult-to-treat pediatric OCD [113]. Lamotrigine is an antiepileptic drug and also a mood stabilizer that decreases extreme glutamate release [114,115].…”
Section: Medical Treatmentmentioning
confidence: 90%